Motivação e habitação : aspectos motivacionais na remoção de favelados - Freitas, Carmencita de Almeida (1986)
The central objetive of this work is to verify the applicability of Abraham. Maslow's theory of motivation (1954) to the experience of slumdwellers in Rio de Janeiro relocated to a government housing project. The study uses a sample of 95 families, residents of the 'Favela da Mare', a shantytown built on stilts over the shallow waters of the bay. In 1982 the agency PROMORAR/PROJETO RIO relocated these families to the community Vila do João. It was hipothesyzed that subject families would develop additional 'needs' once their need for security was satisfied by becoming homeowners. To test the hypothesis subject families were interviewed both before and after the move. A parellel experiment was also realized employing ordinal scales to measure the variables 'need', 'expectation' and 'satisfaction'. The results obtained demonstrate a relation between Maslow's predictions and the responses of shantydwellers to relocations.